Evaluasi Kinerja Instalasi Pengolahan Air Minum (IPA) Universitas Andalas - Komala, Puti Sri; Nur, Ansiha; Fitria, Irna Rosa (Universitas Andalas, 2024)
Universitas Andalas Water Treatment Plant (WTP Unand) is a water treatment plant that serves the drinking water needs of Universitas Andalas with a 90 L/second capacity. WTP Unand has been operating for decades so it is necessary to evaluate the performance and operation of the drinking water treatment system to ensure the quantity and quality of the treated water. This study aims to measure the performance of the Unand WTP unit, analyze the quality of production water produced based on Permenkes No.2/2023 standards for drinking water quality parameters, and analyze the design of the Unand WTP at development discharge. The future flow rate is determined based on the Master Plan of Universitas Andalas in 2030. Based on the analysis of current water demand (year 2023), the flow rate distributed is insufficient. Of the existing water treatment units in WTP Unand, only the Slow Sand Filter (SSF) unit meets the design criteria of the Indonesian National Standard (SNI) 3981: 2008, while the WTP package unit and the Rapid Sand Filter (SPC) unit do not meet the design criteria according to SNI 6774: 2008 at existing and future flow rates. The water quality analysis of WTP Unand found that Total Dissolved Solid (TDS), turbidity, and Total Coliform parameters did not meet the quality standards. The omission of coagulation and disinfection is one of the reasons why some water quality parameters are not compliant. Evaluation of the design criteria of the WTP unit at an increased discharge of 32 L/sec was not fulfilled, so further resizing and redesign of the treatment unit were required.Keywords: Drinking Water Quality, Evaluation, Performance, Water Treatment Plant (WTP) ABSTRAKInstalasi Pengolahan Air Universitas Andalas (IPA Unand) merupakan instalasi pengolahan air yang melayani kebutuhan air bersih Universitas Andalas dengan kapasitas 90 L/detik. IPA Unand sudah beroperasi beberapa dekade sehingga perlu dilakukannya evaluasi kinerja serta operasional sistem pengolahan air minum untuk menjamin kuantitas dan kualitas air yang diolah. Penelitian ini bertujuan mengukur kinerja unit IPA Unand, analisis kualitas air produksi yang dihasilkan berdasarkan standar Permenkes No.2/2023 untuk parameter kualitas air minum dan analisis desain IPA Unand pada debit pengembangan. Debit pengembangan ditentukan berdasarkan Master Plan Universitas Andalas di tahun 2030. Berdasarkan analisis kebutuhan air Universitas Andalas eksisting, debit aliran air yang didistribusikan masih tidak mencukupi kebutuhan. Dari unit-unit pengolahan air yang ada di IPA Unand, hanya unit Saringan Pasir Lambat (SPL) yang memenuhi kriteria desain SNI 3981:2008, sementara pada unit paket IPA dan pada unit Saringan Pasir Cepat (SPC) tidak memenuhi kriteria disain menurut SNI 6774:2008 pada debit eksisting maupun pengembangan. Hasil analisis kualitas air pengolahan IPA Unand ditemukan parameter Total Dissolved Solid (TDS), kekeruhan, dan Total Coliform tidak memenuhi baku mutu. Tidak dilakukannya koagulasi dan desinfeksi merupakan salah satu alasan mengapa beberapa parameter kualitas air tidak memenuhi syarat. Evaluasi kriteria desain unit IPA pada peningkatan debit sebesar 32 L/detik tidak terpenuhi, sehingga diperlukan perubahan dimensi dan desain ulang unit pengolahan lebih lanjut.Kata kunci: Evaluasi, Kinerja, Kualitas Air Minum, Instalasi Pengolahan Air (IPA)